2016
DOI: 10.4067/s0717-95022016000100011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Malnutrition Diet During Lactation Period Leads to Incomplete Catch-Up Growth in Femur of the Pups at Adulthood

Abstract: SUMMARY:The aim of this study was to evaluate the effects of maternal protein and energy restriction during lactation, analyzing on morphological dimensions whether there was catch-up growth through normative nutrition restored, as well as on mechanical axis of femur of the offspring at adulthood. At parturition, Wistar rat dams were randomly assigned to the following groups: 1) control group (C) -free access to a standard laboratory diet containing 23 % protein, 2) protein-energy restricted group (PER) -free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Several studies have proposed that maternal malnutrition during pregnancy [8], the lactation period [9][10][11] or during both timeframes [12][13][14] can cause several developmental changes in multiple tissues of the offspring.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have proposed that maternal malnutrition during pregnancy [8], the lactation period [9][10][11] or during both timeframes [12][13][14] can cause several developmental changes in multiple tissues of the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies evaluated the central nervous system (CNS) and behavioral changes [13,14], while other studies observed changes in muscle tissue [12] and bony tissue [10,11,15], although regarding bones, most of these studies performed morphometric evaluations of the studied bones (e.g. femur, cranium).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators have shown that the nutritional status of the mother during gestation and lactation is essential for normal growth and development, both in human and in experimental animals. 1,2 Previous studies have shown that maternal undernutrition during lactation can cause alterations in breast milk composition, 2 and serum hormone concentrations, 3 which can lead to a reduction in body weight. 2,3 Rats are used as a model for studying human skeletal system and major bone diseases and are considered as a good model for nutritional research.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the study of protein malnutrition effects on mandible is worthwhile, considering the prevalence of this condition in patients, especially in developing countries. 1,12,13 Thus, the objective of this study was to evaluate the effects of maternal protein restriction during lactation on the horizontal and vertical bone growth of the mandible of the pups in adulthood.…”
Section: Introductionmentioning
confidence: 99%